ANALYSIS AND ASSESSMENT OF ANTHROPOGENIC OVERLOADING OF RIVERS IN THE RA (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
In this article it has been given the characteriztic of anthropogenic overloading of the rivers. In the territory of Armenia has been analyzed and assessed the degree of anthropogenic overloading of relatively large rivers for the first time. The rivers have been grouped according to the degree of anthropogenic overloading; weak, medium and strong, and the schematic map of spatial distribution of the rivers' overloading has been created.
Keywords: river discharge; hydroecology; population numbers; anthropogenic overloading of the rivers